Developing a Local-Based Book as a Supplementary English Teaching Material for Undergraduate Students - Stella Prancisca; Muhammad Ainur Rizqi (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
The present paper develops an English reading book that embeds local values of West Kalimantan Province of Indonesia, represented by plants used by local people for medication. The book will help language learners in two ways. First, it helps the learners with familiar information which they have found in their daily lives. Second, this book tries to preserve the local culture among millennial students who are immensely exposed to western lifestyles. ADDIE model of material development was adopted in the paper. The present paper only discusses the first three stages of the model. 40 participants of a university in West Kalimantan Province were invited to take part in the need analysis stage. They were requested to voluntarily fill questionnaires which included their personal information, reading habit, and familiarity towards West Kalimantan medicinal plants. The results of the questionnaires assisted the researchers to visualise the needs of the learners before the book was actually designed. It helped us set the book content, format, and level of difficulty. On top of that, the results informed the researchers on parts of the questionnaires that should be improved and items that should be excluded. Keywords: Extensive reading, Home remedy, Material development